A Review of Wood Dust Longitudinal Health Studies: Implications for an Occupational Limit Value - Stewart E. Holm; John L. Festa (SAGE Publishing, 2019)
Numerous studies reporting on the health effects of wood dust have been published over many decades. For the clear majority of these studies, their use for setting a science-based occupational exposure level is problematic due generally to insufficient exposure measurement data, inadequate participant follow-up, and lack of control for confounding variables. However, there exists a robust data set from a large longitudinal lung function study that provides a scientifically sound basis for establishing an occupational limit of 5 mg/m 3 inhalable wood dust. The choice of this data set and its application for this purpose are presented in this review.